G134(P) The impact of the cardiff and vale e-mail advice service at the primary-secondary care interface. (24th May 2017) - Bhattacharjee, D; Voort, J van der; Hanna, D
Abstract : Introduction: Evidence suggests that health systems with integrated paediatric care deliver improved outcomes for children and help to reduce inequities in healthcare provision. Cardiff and Vale (CAV) Paediatric e-advice is a step towards integrating paediatric care between GPs and Paediatricians. This is a proof of concept evaluation of the introduction and usage of e-Advice. Methods: Two paediatric trainees provided answers to GP queries via e-Advice, with supervision from a Consultant Paediatrician. Using the existing IT system incorporated within e-Advice, data was obtained on the total number of e-advice conversations with a weekly breakdown; response times to queries; and outcomes of the e-Advice dialogues. User satisfaction was also evaluated using a qualitative questionnaire to all GPs who had used the service. Trainee feedback regarding delivery of the service was also taken into account. Results: Between 16 th February and 12 th August 2016, 114 eadvice conversations took place. The outcomes of these dialogues showed that 68% of dialogues resulted in advice being given to the GP to continue their management of the patient in primary care, with 17% resulting in advice to refer the child to General Paediatric outpatients. 93% of queries are responded to within 48 hours of sending. Qualitative feedback showed that 100% of respondents stated they found e-advice a useful service and also would use e-advice again. Free text feedback was almost exclusively positive, with the main themes centred on speed of reply; appropriate avoidance of referral; and high educational value. Conclusion: CAV e-Advice has proved itself to be a feasible service for GPs delivered by Paediatricians. Even though it is too early to know whether there is an impact on referral rates to Paediatric outpatients, it is a service that has had very positive feedback from GPs, and has also served as an excellent training tool for both GPs and Paediatric trainees, which will encourage integrated care. Job planning will be required to incorporate the time needed to deliver a high quality service within the General Paediatric consultant's workload, but this is achievable given the benefits of the service, both immediate and long-term.